Catalytic hydrothermal deoxygenation of the lipid fraction of activated sludge. Issue 8 (14th September 2021) - Edeh, Ifeanyichukwu; Overton, Tim; Bowra, Steve
Abstract: The need for sustainable wastewater treatment and search for cheap feedstock for renewable energy production have driven investigators to evaluate the potential of producing biofuels from waste materials such as sewage sludge. The current work is aimed at assessing the potential for producing hydrocarbons from the lipid fraction of activated sludge via a catalytic hydrothermal decarboxylation reaction under varying residence time. Impacts of platinum on carbon (Pt/C) and palladium on carbon (Pd/C) catalysts were evaluated at 290 °C and residence time of 0.5, 1, 3 and 4 h. The analyses of the lipids and hydrocarbons were done using high-temperature gas chromatography. The results show that at the optimum conditions of 1 h, 290 °C, 20 mg of catalyst, 100 mg of lipid extract and 15 mL of water, the maximum yield of hydrocarbon was 23.2% of pentadecane obtained using Pt/C. This shows that the dominant hydrocarbon is pentadecane and that Pt/C exhibited greater catalytic effect than did Pd/C. The hydrocarbons might be used directly as renewable diesel and as such will contribute to the mitigation of climate change since emission of greenhouse gases will be reduced, and the use of activated sludge as the feedstock is expected to help minimize the cost of production and to ensure sustainable wastewater treatment.